Isolated IgG4-related sclerosing cholangitis mimicking hilar cholangiocarcinoma: a case report of a challenging disease - Kumar, Dinesh; Sana, Sana; Shariq, M.; Dhabalia, Nimit (International Journal of Research in Medical Sciences, 2023)
IgG4-related disease (IgG4-RD) has recently attracted attention worldwide; however, its diagnosis still remains challenging. It is an immune-mediated multisystem disease affecting a wide range of organs in the human body. Even though it’s uncommon, IgG4-sclerosing cholangitis, which is a biliary manifestation of IgG4-RD, can happen without pancreatic involvement. Here, we report a case of a patient with imaging features typical of hilar cholangiocarcinoma, which eventually turned out to be IgG4 sclerosing cholangitis.